(untitled) (Experimental biology, 2009)
There are the changes described in organism poisoned by hydrazine’s derivates (nitrosodimethylaminum, acidic isonicotinum’s gidrazidum, fenylhydrazidum, hydrazine sulfatum ) in this article. During the intoxication they had been determined changes in the structures of the brain